Advancing or postponing the day of human chorionic gonadotropin does not matter for the outcome in assisted reproductive technology - Pratap, Deepika (Medknow Publications & Media Pvt Ltd, 2014)
CONTEXT: The primary outcome is to remove the worry of getting immature oocytes with early administration of human chorionic gonadotropin (hCG). AIM: The aim was to find out the association between the day of hCG administration and follicular response in relation to the number and maturity of oocytes, and fertilization rate in assisted reproduction to avoid weekend oocyte recovery (OR). SETTINGS AND DESIGN: Retrospective study was carried out in the university infertility clinic. MATERIALS AND METHOD: Controlled ovarian hyperstimulation (COH) in 94 patients undergoing assisted reproductive technology (2010-2011) with recombinant follicle stimulating hormone and timely gonadotropin-releasing hormone antagonist were analyzed regarding day of hCG from day 8-11. Oocyte maturity and fertilization was analyzed and correlated with the day of hCG administration. STATISTICAL ANALYSIS: Kruskal–Wallis test. RESULTS: The average number of >18 mm follicles observed from day 8-11 of hCG administration was not statistically different. However, the OR rate (54.2%), number of mature oocytes (92.5%), and fertilization rate (78.5%) was maximum in the patients where hCG was administered on day 8 of COH. CONCLUSIONS: The day of hCG administration between 8 and 11 does not affect the OR rate significantly although the number of oocytes recovered on day 8 are marginally higher compared with day 9-11. Hence, it is possible to safely avoid weekend oocyte retrieval, by delaying or advancing hCG administration without compromising the outcome.